Host modulation by therapeutic agents - Sugumari Elavarasu; Santhosh Sekar; Thamaraiselvan Murugan (Wolters Kluwer Medknow Publications, 2012)
Periodontal disease susceptible group present advanced periodontal breakdown even though they achieve a high standard of oral hygiene. Various destructive enzymes and inflammatory mediators are involved in destruction. These are elevated in case of periodontal destruction. Host modulation aims at bringing these enzymes and mediators to normal level. Doxycycline, nonsteroidal anti-inflammatory drugs (NSAIDs), bisphosphonates, nitrous oxide (NO) synthase inhibitors, recombinant human interleukin-11 (rhIL-11), omega-3 fatty acid, mouse anti-human interleukin-6 receptor antibody (MRA), mitogen-activated protein kinase (MAPK) inhibitors, nuclear factor-kappa B (NF-kb) inhibitors, osteoprotegerin, and tumor necrosis factor antagonist (TNF-α) are some of the therapeutic agents that have host modulation properties.